2009
DOI: 10.1088/0022-3727/42/16/165001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization reversal and magnetic interactions in patterned spin valve structures

Abstract: We have investigated the magnetization reversal and the magnetic anisotropy of epitaxial Co(1 12 0) and Fe(0 0 1) films and compared them with epitaxial Co(1 12 0)/Cr(0 0 1)/Fe(0 0 1) trilayers with spin valve characteristics. Furthermore, by e-beam lithography we have cut the single layers and the trilayers into the shape of wires to study the effect of the shape anisotropy and the dipolar interaction between the wires on their switching characteristics. We found that patterning very much affects the magnetiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…29,30 The asymmetric superlattice consists of two different ferromagnetic layers with a total of eight repetitions and a layer sequence of [Fe/Cr/Co/Cr] Â 8 with nominal thicknesses according to the values in Table I. The sample was grown at a temperature of 300 C on MgO(100) single crystal substrates by use of a 25 nm thick Cr(100) buffer layer deposited at substrate temperature of 600 C. More details of the sample growth conditions can be found in Ref.…”
Section: Sample Design and Structural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 The asymmetric superlattice consists of two different ferromagnetic layers with a total of eight repetitions and a layer sequence of [Fe/Cr/Co/Cr] Â 8 with nominal thicknesses according to the values in Table I. The sample was grown at a temperature of 300 C on MgO(100) single crystal substrates by use of a 25 nm thick Cr(100) buffer layer deposited at substrate temperature of 600 C. More details of the sample growth conditions can be found in Ref.…”
Section: Sample Design and Structural Characterizationmentioning
confidence: 99%
“…The sample was grown at a temperature of 300 C on MgO(100) single crystal substrates by use of a 25 nm thick Cr(100) buffer layer deposited at substrate temperature of 600 C. More details of the sample growth conditions can be found in Ref. 29. The thickness of the Cr interlayers was chosen to mediate a weak antiferromagnetic (AF) coupling between the Fe and the Co layers, as reported in Ref.…”
Section: Sample Design and Structural Characterizationmentioning
confidence: 99%
“…[32][33][34] For the more general magnetic properties of the trilayer including magnetic hysteresis measurements we refer to our earlier study reported in Ref. 25.…”
Section: Magnetic Polarization Of Crmentioning
confidence: 99%
“…The present study amends earlier investigations of Co/Cr/Fe trilayers via the magnetooptic Kerr effect (MOKE). 18,19 In these previous studies, we have established the range of interlayer exchange coupling between Fe and Co layers across the mediating Cr layer 18 and the magnetization reversal process of single Fe and Co layers as compared to the coupled layers using vector MOKE. 19 Before we discuss our present results in Secs.…”
Section: Introductionmentioning
confidence: 99%